Comparative Study Of Structure Response Isolated Base And Not Isolated Base on IHF School Cimanggis - Munthe, Agyanata Tua; Iksan, M (Journal of World Conference (JWC), 2020)
Along with technological developments in the field of civil engineering, various systems are used to reduce the impact of earthquakes on the structure. One system that has long been developed is a passive prevention system consisting of seismic isolation. Buildings that use seismic dumper are expected to fail structure when an earthquake occurs. This study discusses the comparison of internal forces in buildings using base isolation and without base isolation. The building which is the case study is the Indonesian Heritage Foundation school building in Cimanggis. The analysis uses the 2016 ETABS program. Earthquake analysis uses the Spectrum Response method. From the research results, it is known that the building which was installed with an insulator shakes the structure to 1,344 seconds. The vibration period of the structure increased 41% from the vibration period of the structure which still used a fixed base of 0.796 seconds. Seen from the intersection between floors the maximum direction of X can be reduced by 15.4% by installing an insulator. The same thing happened to the maximum inter-floor deviation for the Y direction deviation is muted by 27.75%. Base isolation installation reduces the moment in a column by 36% in the earthquake X direction and 61% in the earthquake Y direction. For column shear force is reduced by 58% in the earthquake X direction and 75% in the earthquake Y direction. Base isolation can reduce basic shear force in buildings by 24.49% in the X direction of the building and 22.24% in the Y direction.